Design, fabrication and characterization of nanocaged 12CaO·7Al2O3:Tb3+ photostimulable phosphor for high-quality X-ray imaging. (15th November 2017) - Li, Shengnan; Liu, Yuxue; Liu, Chunguang; Yan, Duanting; Zhu, Hancheng; Yang, Jian; Zhang, Meng; Xu, Changshan; Ma, Li; Wang, Xiaojun
Abstract: It has been a challenge to realize high-quality X-ray imaging using oxide-based phosphors for avoiding halogenide-based materials and satisfying the requirements of environmental protection. In this study, lanthanide-doped nanocaged 12CaO·7Al2 O3 :Tb 3+ (C12A7:Tb 3+ ) X-ray imaging phosphors with strong photostimulated luminescence (PSL) have been prepared using a combustion method. X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDS), Fourier transform infrared (FTIR) spectra, scanning electron microscopy (SEM) and transmission electron microscope (TEM) measurements suggest that single-phased C12A7:Tb 3+ powders with an average grain size ranging from several hundred nanometers to several micrometers have been obtained at the ignition temperature from 700 to 900 °C. PSL, thermoluminescence (TL), electron spin resonance (ESR) and photoconductivity analyses indicate that the storage time of X-ray image exceeds 48 h due to the existence of deep traps in the C12A7:Tb 3+ phosphor. High-quality X-ray imaging with a resolution of 15 line pairs per mm has been achieved using the phosphor. High conversion efficiency is achieved at 1.28 pJ/mm 2 /mR, suggesting the application potential of the phosphors in X-ray imaging and medical diagnostics. Graphical abstract: Highlights: Nanocaged C12A7:Tb 3 + phosphors with sub-micrometer grain size were prepared. The residence time of the electrons trapped in the deeper traps exceeds 48 h. The conversion efficiency of the phosphor is ~ 1.28 pJ/mm 2 /mR. The high-quality X-ray image is related to the cubic structure of C12A7.